COGNITIVE IMPAIRMENT CAUSED BY HYPERBILIRUBINEMIA IN ADULT PATIENTS WITH MECHANICAL JAUNDICE SECONDARY TO CHOLEDOCHOLITHIASIS - Maksymenko, Mykhailo; Havryliuk, Roman (Eastern Ukrainian Medical Journal, 2025)
Background. The neurotoxic effects of bilirubin are well-documented in neonatal jaundice, where hyperbilirubinemia can lead to kernicterus and long-term neurodevelopmental deficits. However, the cognitive impact of hyperbilirubinemia in adults, particularly in the context of mechanical jaundice, remains poorly understood. With the rising prevalence of choledocholithiasis due to lifestyle changes and an aging population, understanding the neurological consequences of this condition is becoming increasingly important. Objectives. This study aimed to characterize the extent and nature of cognitive dysfunction in adult patients with choledocholithiasis-induced mechanical jaundice and associated hyperbilirubinemia; evaluate the correlation between serum bilirubin concentrations and cognitive performance metrics; and determine the potential reversibility of observed cognitive deficits following therapeutic biliary decompression. Materials and Methods. Cognitive function was assessed in adult patients with mechanical jaundice secondary to choledocholithiasis using the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA). Initial evaluations were conducted after hospitalization, with follow-up assessments performed one week after successful biliary decompression via percutaneous transhepatic cholangiostomy (PTCH) or endoscopic/surgical intervention. Results. Patients with mechanical jaundice exhibited significantly lower cognitive scores compared to the control group at baseline. A moderate-to-strong positive correlation was identified between total bilirubin levels and the severity of cognitive impairment. Following biliary decompression, cognitive function improved markedly. However, 10.2% of patients experienced persistent mild cognitive deficits despite normalization of bilirubin levels. Conclusions. Hyperbilirubinemia in adults with mechanical jaundice caused by choledocholithiasis is associated with significant but predominantly reversible cognitive impairment. Early recognition and management, including timely biliary decompression and supportive therapy, are crucial for improving neurological outcomes and enhancing the overall quality of life for affected patients.